Use of an isometric mid-thigh pull test during musculoskeletal rehabilitation: can the criterion values from the updated British Army physical employment standards be used to inform UK Defence Rehabilitation practice?. Issue 4 (20th August 2021) - Walters, Vanessa; Coppack, RJ; Cassidy, RP; Suffield, C; Papadopoulou, T; Bilzon, J; Ladlow, P
Abstract : Introduction: Objective outcome measures that can quantify the force generating capacity of the lower limb are required to allow clinicians to accurately measure functional status and treatment adaptations over time. The aim of this prospective observational cohort study is to: (1) evaluate the acceptability of the isometric mid-thigh pull (IMTP) test as a measure of functional strength with military personnel undergoing residential hip pain rehabilitation; (2) compare the peak force values recorded against the updated Army physical employment standards (PES) assessment criteria and (3) assess if the minimum PES required of military personnel has the potential to inform clinical decision making and return to duty criteria within UK Defence Rehabilitation. Methods: Acceptability was assessed against patient's adherence to the testing procedures and test burden. Clinician acceptability was assessed against ease of administration and safety of test procedure. Hip pain was recorded before, immediately following and 1 hour after testing. Net peak force was recorded using portable force plates. Results: Full patient and clinician acceptability to IMTP testing procedures were demonstrated. Minimal changes in visual analogue scale (VAS) pain scores were demonstrated between baseline values at rest and follow-up. Despite being medically downgraded and functionally compromised due to chronic hip pain, 100% of patients met the PES expected on entry to the British Army and 79% met the PES expected at the end of basic training. Conclusion: The IMTP provides rehabilitation clinicians with an objective quantifiable measure of maximum muscle strength that can be used early in the rehabilitation care pathway. Based on our finding, it is unclear if the current British Army PES can be used as a criterion standard in Defence Rehabilitation. Therefore, further research focused on generating clinically relevant patient-specific IMTP score criteria, with a larger sample of diverse diagnostic sub-groups is required.